2008
DOI: 10.1007/s10517-009-0349-x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Interferon Production by Conformation-Modified Proteins of Plasma γ-Globulin Fraction

Abstract: Plasma gamma-globulin fraction proteins, copper and zinc cations, and metal-modified gamma-globulins induce the production of IFN by human leukocytes. Binding of zinc cations attenuates the realization of the IFN-inducing effects of human serum gamma-globulin, while binding of copper cations potentiated this effect. Activity of IFN and the dynamics of its production correspond to those in response to phytohemagglutinin stimulation. The pool of induced IFN contains acid-labile (up to 60%) and acid-stable (up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…The same regularities were observed under conditions of late induction with predominant production of IFN-γ, when zinc reduced and copper stimulated the manifestation of IFN-inducing activity of γ-globulin, binding these cations. In parallel, zinc lost its own IFN inductor potential, while copper (presumably) realizes its potential even as a component of the protein-metal complex [4].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The same regularities were observed under conditions of late induction with predominant production of IFN-γ, when zinc reduced and copper stimulated the manifestation of IFN-inducing activity of γ-globulin, binding these cations. In parallel, zinc lost its own IFN inductor potential, while copper (presumably) realizes its potential even as a component of the protein-metal complex [4].…”
Section: Resultsmentioning
confidence: 99%
“…The content of IFN-α in supernatants of induced leukocytes reached 60-90 pg/ml and correlated with antiviral activity of the samples. Zinc bound to human serum γ-globulin attenuated and copper stimulated the realization of IFN-inducing characteristics of the protein at early terms of incubation.Previous studies showed that the pool of IFN produced in the presence of plasma γ-globulin fraction proteins contains mainly the cytokine corresponding to IFN-γ by its properties [4]. Metal-specific conformation changes of Fc region of the antibody molecule caused by incorporation of copper or zinc cations [5] potentiate or attenuate the effect of IFN induction by the protein which bound the metal and was modified by it [4].…”
mentioning
confidence: 99%
See 3 more Smart Citations